Entrepreneurship Education as Mediator of the Reletionship between Entrepreneurial Orientation and Entrepreneurial Intentions ofStudents - Benchikh, Boubaker (Milev Journal of Research and Studies, 2021)
The objective of this study was to examine the impact relationship between entrepreneurial orientation and entrepreneurial intentions of students, and examine the moderating effect of entrepreneurship education on the relationship between entrepreneurial orientation and entrepreneurial intentions. Quantitative research method (survey) was used to solicit from 371 students of university of jijel. The results indicated that entrepreneurial orientation had significant positive influence on entrepreneurial intention among students; it was also found that entrepreneurship education, moderated the relationship between entrepreneurial orientation and entrepreneurial intentions among the students.